Perception of quality and familiarity in the retail service environment, and its impact on patronage intention - Bizarrias, Flávio; Santos, Cintia Rosa dos; Ferreira, Marlette Cassia Oliveira; Cucato, Jussara da Silva Teixeira; Silva, Jussara Goulart da (Retail Management Review, 2023)
Objective of the study - The aim of this study is to investigate the mediating role of perceived quality and service satisfaction on the relationship between brand familiarity and patronage intention towards retail stores. Methodology/approach - Through a survey of 400 respondents, this study employed structural equation modeling and mediation tests to test the direct and conditional hypotheses. Findings- Perceived service quality acts as an important mediator in the link between familiarity and patronage intention. Satisfaction is also a mediator, but perceived quality is more important. In addition, consumer response to patronage intention is stronger when influenced by satisfaction than directly by perceived quality Theoretical/methodological contributions - The study advances knowledge about quality in services, as a mediating mechanism for familiarity and impacts on favorable consumer responses. Relevance/originality - The study is a pioneer in proposing the relationship between familiarity and quality in services.